Olive fruits infested with olive fly larvae respond with an ethylene burst and the emission of specific volatiles. Issue 4 (18th April 2015) - Alagna, Fiammetta; Kallenbach, Mario; Pompa, Andrea; De Marchis, Francesca; Rao, Rosa; Baldwin, Ian T.; Bonaventure, Gustavo; Baldoni, Luciana
Abstract: Olive fly ( Bactrocera oleae R.) is the most harmful insect pest of olive ( Olea europaea L.) which strongly affects fruits and oil production. Despite the expanding economic importance of olive cultivation, up to now, only limited information on plant responses to B. oleae is available. Here, we demonstrate that olive fruits respond to B. oleae attack by producing changes in an array of different defensive compounds including phytohormones, volatile organic compounds (VOCs), and defense proteins. Bactrocera oleae‐infested fruits induced a strong ethylene burst and transcript levels of several putative ethylene‐responsive transcription factors became significantly upregulated. Moreover, infested fruits induced significant changes in the levels of 12‐oxo‐phytodienoic acid and C12 derivatives of the hydroperoxide lyase. The emission of VOCs was also changed quantitatively and qualitatively in insect‐damaged fruits, indicating that B. oleae larval feeding can specifically affect the volatile blend of fruits. Finally, we show that larval infestation maintained high levels of trypsin protease inhibitors in ripe fruits, probably by affecting post‐transcriptional mechanisms. Our results provide novel and important information to understand the response of the olive fruit to B. oleae attack; information that can shed light onto potential new strategies to combat this pest. Abstract : Olive fly ( Bactroceraoleae R.), the most harmful insect pest of olive ( Olea europaea L.), strongly affects fruits and oil production. We demonstrate that olive fruits respond to B. oleae attacks by producing changes in an array of different defensive compounds including phytohormones, volatile organic compounds(VOCs), and defense proteins.